Community-Based Social Containment as a Strategy to Prevent The Coronavirus Disease (Covid-19) - Andi Nuriyanto; Laili Rahayuwati; Mamat Lukman (Universitas Padjadjaran, 2021)
Various efforts have been made optimally in suppressing the upsurge number of the Coronavirus Disease (COVID-19) outbreak, but the incidence of confirmed cases continues to increase. Lack of understanding, awareness, and effective communication from the public in responding to the dangers and spread of COVID-19 requires the participation of the community to work together to create strategies to reduce the increase in confirmed cases. Research on community-based prevention of the spread of COVID-19 is still very minimal; more information is needed so that it can be the basis for determining new, more appropriate strategies. This article was written using a literature review method. The aim of this research is to find strategies to prevent the spread of COVID-19 at the community level. The entire article is a non-experimental study and is cross-sectional and observational from the Google Scholar, PubMed, and ERIC (EBSCO) database with a total of nine analysis articles originating from China, Australia, Italy, Indonesia and Saudi Arabia. Keywords used to determine articles are English